THE RELATIONSHIP BETWEEN CEO DUALITY AND FIRM PERFORMANCE IN LIGHT OF BOARD SIZE AS A MODERATOR - Salim, Shahad (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2023)
This research investigates the intricate link between CEO duality and company performance in Texas service organizations while illuminating the moderating role of the number of directors. To accomplish this, the study conducts a comprehensive analysis using a dataset of Texas service companies over a specific time frame. Rigorous statistical methods, including multiple regression analysis and moderation analysis, are employed to assess the relationship between CEO duality, board size, and company performance. Various performance metrics, such as return on assets (ROA), return on equity (ROE), and Tobin's Q ratio, are used to measure business performance. Panel data from 2018 to 2020 are gathered from published accounts, and the research utilizes IGLS regression models to test the theory. The findings reveal a complex relationship between CEO duality and business performance in Texas service firms, with CEO duality significantly correlated with firm performance, and board size playing a substantial moderating role. This study offers valuable guidance to the boards of directors and executives of Texas service organizations on optimizing board sizes and governance structures to enhance company performance. It also advances our understanding of the nuanced interactions between CEO duality and board size within the broader corporate governance literature, emphasizing the context-specific nature of these effects. Additionally, this research contributes to the field by examining these dynamics within the unique context of Texas service organizations, shedding light on their distinct characteristics and governance requirements compared to businesses in other regions or industries.